Development and auxetic characterization of 3D composites produced with newly-designed multi-cell flat-knitted spacer fabrics. Issue 2 (June 2022) - Moshtaghian, Zahra; Hasani, Hossein; Zarrebini, Mohammad; Pourheidar Shirazi, Mohammad
The paper deals with development and characterization of 3D sandwich composite structures reinforced with newly-designed multi-cell flat-knitted spacer fabrics in terms of compressive behaviour and Poisson's ratio. Multi-cell spacer knitted preforms was produced on a computerized flat knitting machine. 3D composite samples with three different cross-sectional geometries were prepared via vacuum assisted resin transfer moulding method. Quasi-static compressive experiments were carried out on the prepared 3D composite samples. The Poisson's ratio of re-entrant 3D knitted composite varied between -6 and -1, which clearly points to existence of auxetic behaviour of the samples. The re-entrant 3D composites also demonstrated the highest initial slope and area under the compression force-displacement curve than spear-head or hexagonal composite structures which refer to higher energy absorbing capacity. The Poisson's ratio of 3D regular hexagonal knitted composites at small strain was usually 4 which gradually decreased to 1.6 as the exerted compressive strain increased. Additionally, 3D spear-head knitted composite having zero Poisson's ratio was also developed.